2011
DOI: 10.5433/1679-0359.2011v32n4p1595
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho, consumo e digestibilidade de cordeiros em confinamento recebendo silagens de capim elefante com diferentes proporções de casca desidratada de maracujá

Abstract: The consumption, digestibility, and performance was evaluated of lambs fed silage elephant grass containing different inclusion levels of passion fruit peel dried (0, 10, 20 and 30%) in natural matter of elephant grass, in a randomized completely randomized design with four replications. The elephant grass was cut at 60 days of age, chopped and ensiled in barrels along with the proportions of dried passion fruit peel, according to each treatment. After 30 days, the silos were opened for evaluation. It was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…The maximum inclusion level (40%) estimated by the equation was 0.488 g, which means the ovine consumed 0.288 kg more than in control treatment (0.260 kg). Reference [ 16 ], assessing elephant grass silage with different proportions of dehydrated passion fruit husk, in lamb diet, observed that the NDF consumption in kg/day increased from 0.004% for each 1% of passion fruit husk included in grass silage, values close to the ones observed in the present study.…”
Section: Resultssupporting
confidence: 90%
“…The maximum inclusion level (40%) estimated by the equation was 0.488 g, which means the ovine consumed 0.288 kg more than in control treatment (0.260 kg). Reference [ 16 ], assessing elephant grass silage with different proportions of dehydrated passion fruit husk, in lamb diet, observed that the NDF consumption in kg/day increased from 0.004% for each 1% of passion fruit husk included in grass silage, values close to the ones observed in the present study.…”
Section: Resultssupporting
confidence: 90%
“…Segundo Moreno et al (2010) e Cruz et al (2011), a ingestão e a digestibilidade dos nutrientes podem estar correlacionados de maneira positiva ou negativa entre si, o que depende da qualidade da dieta, comumente referidos como efeitos associativos. Normalmente, a correlação entre a ingestão e a digestibilidade dos nutrientes é positiva em ditas com elevada proporção de volumoso de baixa qualidade, uma vez que o volume ocupado pela fração fibrosa de baixa digestibilidade reduz a ingestão de matéria seca ( VAN SOEST, 1994).…”
Section: Introductionunclassified
“…According to Moreno et al (2010) and Cruz et al (2011), the intake and digestibility of nutrients can be correlated positively or negatively with each other, depending on the quality of the diet, commonly referred to as associative effects. In the same way, Goularte et al (2011) stated that the intake and digestibility of nutrients might be correlated with each other according to the quality of the diet.…”
Section: Methodsmentioning
confidence: 99%